KEBIJAKAN PEMBANGUNAN DESA MELALUI PEMBANGUNAN INFRASTRUKTUR TRANSPORTASI DALAM UPAYA PEMERATAAN PEMBANGUNAN DI DESA PLESUNGAN KECAATAN KAPAS KABUPATEN BOJONEGORO - Amni Zarkasyi Rahman; Diyah Novitasari (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2018)
Law of Republic Indonesia Number 6 of 2014 concerning Villages as one of development policy raises an implication in the budgeting system, namely the emergence of The Village Funds (VF) and Village Fund Allocation (VFA) in the components of the Village Budget (APBDes). One of the objectives of the Village Law through VF and VFA is to ensure that basic infrastructure such as roads, canals, dikes, electricity and clean water in the village have been fulfilled so as to be able to support the smooth economic activities of the village. The road which is one of the basic infrastructure related to transportation and accessibility is key in the economy of a region. The existence of a good road facilitates access to an area and the community can more easily carry out their activities. This will certainly have a long-term impact on people's lives, one of which is increasing economic growth in the region, one of which can be seen with an increase in Gross Regional Domestic Product (GRDP). The important thing to study more deeply is how the availability of good road facilities in the village is able to contribute to the increase in GRDP.